2023
DOI: 10.3390/ma16072923
|View full text |Cite
|
Sign up to set email alerts
|

Scratch and Wear Behaviour of Co-Cr-Mo Alloy in Ringer’s Lactate Solution

Abstract: Cobalt–chromium–molybdenum (Co-Cr-Mo) alloy is a material recommended for biomedical implants; however, to be suitable for this application, it should have good tribological properties, which are related to grain size. This paper investigates the tribological behaviour of a Co-Cr-Mo alloy produced using investment casting, together with electromagnetic stirring, to reduce its grain size. The samples were subjected to wear and scratch tests in simulated body fluid (Ringer’s lactate solution). Since a reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…reported that micro hardness of knee bone implant material of Lithography-based ceramic recorded as 559 ± 27 HV. The proposed laser cladded sample specimen for knee bone achieved 898.37 HV [ 49 ]. reported that the alternate material of Cobalt–chromium–molybdenum alloy for knee bone implant recorded the wear volume as 0.79 mm.…”
Section: Resultsmentioning
confidence: 99%
“…reported that micro hardness of knee bone implant material of Lithography-based ceramic recorded as 559 ± 27 HV. The proposed laser cladded sample specimen for knee bone achieved 898.37 HV [ 49 ]. reported that the alternate material of Cobalt–chromium–molybdenum alloy for knee bone implant recorded the wear volume as 0.79 mm.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical, electrical, and optical properties of a material are profoundly influenced by both external and internal surface characteristics. Investigating properties such as morphology, crystalline structure, and chemical composition provides insights into the intrinsic qualities of a thin film, thereby shaping its potential for technological applications [6][7][8][9][10]. By manipulating substrate cleaning conditions and deposition parameters in the evaporation chamber, the mentioned parameters can be altered.…”
Section: Introductionmentioning
confidence: 99%
“…By manipulating substrate cleaning conditions and deposition parameters in the evaporation chamber, the mentioned parameters can be altered. Understanding and characterizing the factors influencing PTP adherence to the filter is a crucial step in optimizing coating and cleaning processes to enhance film durability and efficiency [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, changes in the microstructure can affect the mechanical properties. However, microstructure and alloy composition affect corrosion behaviour in simulated body fluids due to changes in surface chemistry [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%